Making Technology Masculine Men, Women, and Modern Machines in America, 1870-1945 - Oldenziel, Ruth (Amsterdam University Press, 1999)
To say that technology is male comes as no surprise, but the claim that its history is a short one strikes a new note. Making Technology Masculine: Men, Women, and Modern Machines in America, 1870-1945 maps the historical process through which men laid claims to technology as their exclusive terrain. It also explores how women contested this ascendancy of the male discourse and engineered alternative plots. From the moral gymnasium of the shop floor to the staging grounds of World's Fairs, engineers, inventors, social scientists, activists, and novelists emplotted and questioned technology as our modern male myth. Oldenziel recounts the history of technology - both as intellectual construct and material practice - by analyzing these struggles. Drawing on a broad range of sources, she explains why male machines rather than female fabrics have become the modern markers of technology. She shows how technology developed as a narrative production of modern manliness, allowing women little room for negotiation.